Remotion of the 17α-Ethinylestradiol Hormone (EE2) by Biosorbent (Arachis hypogaea) in Aqueous Solutions: Validation of Analytical Methodology and Adsorption Study - Procópio, Alley Michael da Silva; Cais, Thayná Aparecida; Da Silva, Waleska Freitas; Kondo, Márcia Matiko; Silva, Flávio Soares; Andrade, Sandro José de (Ciência e Natura, 2022)
This study describes the application of peanut shells, a biodegradable agroindustrial residue as a biosorbent, in the 17α-ethinylestradiol (EE2) removal in water matrices. An analytical method was developed and validated from the high-performance liquid chromatographic technique with fluorescence detection (HPLC-FLD) in a λEx= 230 nm and λEm= 310 nm in the determination of EE2. The evaluated parameters were: selectivity, linearity (R2 = 0.9984 and R = 0.9992), precision (Variation coefficient = 2.90% and 2.95% for the first and second analyst, respectively), accuracy (recovery rate = 100.2 – 110.4%), detection limit (3.4 – 5.0 μg L-1), quantification limit (10.0 – 11.3 μg L-1) and robustness (recovery rate = 98.7 – 115.5%). The chromatographic analysis conditions were: mobile phase (water 2:3 acetonitrile), mobile phase flow (0.5 mL min-1), injection volume (10 µL), column temperature (45ºC) and race time (10 min). An experiment planning (Box-Behnken Model) was carried out for the investigation and verification of the adsorptive capacity of the peanut shells, of which 3 parameters were evaluated (stirring rate, pH and adsorbent mass) on 3 levels. Optimum experimental condition (2 g of adsorbent, pH = 6 and stirring at 500 rpm) with a removal rate of 90% in 24 hours of the process.